RESTORATIVE JUSTICE APPROACH IN LEGAL PROTECTION FOR MEDICAL PERSONNEL AND PATIENTS - Gunawan Widjaja (Adisam Publisher, 2025)
The Restorative Justice approach to legal protection for medical personnel and patients is an alternative to conflict resolution that prioritises dialogue, mediation and restoration of relationships between the parties involved. This model focuses on fulfilling the needs of victims, holding perpetrators accountable, and improving social relations without relying entirely on formal, retributive legal processes. In the context of health care, this approach provides a more humane and effective solution to minimise conflict between medical personnel and patients, especially in cases of misunderstanding or suspected malpractice. By promoting transparency, openness, and empathy, Restorative Justice contributes to improving the quality of health services while maintaining the integrity of the medical profession, and encouraging a more comprehensive sense of justice for all parties.